(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: The mechanisms generating fatty liver disease, a common complication of type 2 diabetes mellitus (T2DM), are poorly understood. In people with T2DM and fatty livers, this study aimed to understand the relationships among insulin resistance (IR), localized adiposity, and fatty acids. Methods: At the Hayatabad Medical Complex in Peshawar, The study included 120 people with T2DM in total. The patients underwent abdominal computed tomography scans to assess regional adiposity, and specimens of blood were taken to assess insulin resistance and fatty acid levels. A diagnosis of fatty liver was made utilizing ultrasonography imaging. Results: The findings revealed a substantial correlation between fatty liver and raised levels of several fatty acids, such as palmitic acid and oleic acid, as well as increased visceral adiposity. Insulin resistance and liver fat were shown to be highly correlated in T2DM patients. Conclusion: According to the results of this research, Due to regional adiposity, resistance to insulin and altered levels of certain fatty acids, persons with T2DM may develop fatty livers. These findings underline the need of preventing and effectively treating fatty liver disease in this group by managing regional adiposity and insulin resistance. Further research is needed to better comprehend the underlying mechanisms and develop specialized therapeutics for treating fatty liver disease in persons with T2DM.